Enteric Ecosystem Disruption in Autism Spectrum Disorder: Can the Microbiota and Macrobiota be Restored? - Slattery, John; F. MacFabe, Derrick; G. Kahler, Stephen; E. Frye, Richard (Current Pharmaceutical Design, 2016)
Background: Many lines of scientific research suggest that Autism Spectrum Disorders (ASDs) may be associated with alterations in the enteric ecosystem, including alterations of the enteric macrobiome (i.e. helminthes and fauna) and changes in predominant microbiome species, particularly a reduction in microbiome species diversity. Methods: We performed a comprehensive review of the literature and summarized the major findings. Results: Alterations in the enteric ecosystem are believed to be due to a variety of factors including changes in the post-industrial society related to decreased exposure to symbiotic organisms, increased human migration, overuse of antibiotics and changes in dietary habits. Changes in the enteric ecosystem are believed to alter metabolic and immune system function and epigenetic regulation. If these changes occur during critical developmental windows, the trajectory of brain development, as well as brain function, can be altered. This paper reviews theoretical models that explain how these perturbations may in isolation or in combination be causative for ASDs as well as the preclinical and clinical studies that support these models. We discuss how these alterations may converge to trigger or exacerbate the formation of an ASD phenotype. We focus on possible preconception, prenatal, perinatal and postnatal factors that may alter the enteric ecosystem leading to physiological disruptions, potentially through triggering events. Conclusion: If these theoretical models prove to be valid, they may lead to the development of practical interventions which could decrease ASD prevalence and/or morbidity.
Keywords: Macrobiome